On the fixed and the persistent against movement and mutation: Of the peculiar way of dealing with the desire for determination in the Tractatus - Carla (Analysis. Journal of Philosophical Research, 2021)
This paper examines the fixity of the simple and discrete objects of Tractatus logico-philosophicus by comparing it with the taste for the imponderable, which neither has an exact measure nor can be separated from the framework of human practices in which it occurs, and the action rooted in practices always in movement that are characteristic of Philosophical Investigations (as well as of other manuscripts produced in its context). I track Wittgenstein’s distances and approaches to movement. The synoptic view that I provide reveals peculiar inclinations to determinacy and indeterminacy that, I argue, guide, respectively, the Tractatus and the Investigations.